Research on the Driving Mechanism of Island Residents' Participation in Ecological Value Co-creation Behaviors and Their Happiness - Liu, Miaoling (Asia Pacific Economic and Management Review, 2025)
Island residents are not only the bearers of ecological impacts but also key stakeholders and potential active participants. Clarifying the driving mechanism of their participation in ecological value co-creation behaviors is the theoretical basis for understanding and promoting the benign governance of the island social ecosystem. This study constructs a research model of the driving mechanism of island residents' ecological value co-creation behaviors and their happiness. Through a questionnaire survey of 160 island residents and data analysis, the study shows that social capital, local attachment, and self-efficacy have a positive impact on ecological value co-creation behaviors, and ecological value behaviors have a positive impact on residents' happiness. Policy and institutional perception and perceived benefits have no relation to ecological value co-creation behaviors. The research results have practical implications for island ecological governance.